The student's solution is incorrect. Let's review each step to identify the error:
-
Original Equation: \[ -3(4−x)+2=x+2 \]
-
Step 1: \[ -12 + 3x + 2 = x + 2 \] This step is correct. The left side simplifies to \(-12 + 3x + 2 = 3x - 10\).
-
Step 2: \[ -10 - 3x = x + 2 \] This step is incorrect. The correct simplification from Step 1 should yield: \[ 3x - 10 = x + 2 \]
-
Step 3: \[ -8 - 3x = x \] This step relies on the incorrect Step 2. Therefore, this step is also incorrect.
-
Step 4: \[ -8 = 4x \] This step also derives from incorrect prior steps and is therefore invalid.
-
Final Answer: \[ x = -2 \] Since the steps leading to this solution are incorrect, the final answer is also incorrect.
Summary of the Error:
The student made an error in Step 2 where they incorrectly rearranged the terms and did not properly simplify the equation from Step 1. The correct equation should have been: \[ 3x - 10 = x + 2 \] This led to an incorrect solution in subsequent steps.
Correct Steps from Step 1:
Starting from: \[ 3x - 10 = x + 2 \]
You would then move \(x\) to the left side: \[ 3x - x = 2 + 10 \] which simplifies to: \[ 2x = 12 \] Thus, \[ x = 6. \]
As a result, the student's friend should tell them they are incorrect, and the error is in Step 2.